Characterization of Fabricated Gold-Doped ZnO Nanospheres and Their Use as a Photocatalyst in the Degradation of DR-31 Dye. (16th May 2022) - Verma, Neha; Jagota, Vishal; Alguno, Arnold C.; Alimuddin,; Rakhra, Manik; Kumar, Pawan; Dugbakie, Betty Nokobi
Abstract : Water contamination is a significant issue in the modern day, caused by the textile dying business, and it has a detrimental impact on living organisms. We report on the manufacture of gold-doped ZnO nanospheres using a simple heat treatment approach and the use of ZnO nanoparticles as photocatalysts for the degradation of methyl orange dye. To increase this degrading activity, Au was utilised as a modifier, and their temperature quenching effect was noticed. One of the most efficient electron grabbers in the conduction band is Au ion. The novelty of this recent research is that it has found that anatase to rutile phase transformation is promoted, and the highest transformation was achieved by using 1.0% of Au, which proves Au-doped ZnO-based nanoparticles are best for this degradation of dyes. The structural, morphological, optical, electrical, and photocatalytic characteristics of the synthesised nanocatalysts were determined. These nanoparticles have a grain size of 45-75 nm. Photocatalytic activity was investigated using UV-Vis spectra, and a significant absorption peak of about 482 nm was discovered. With increasing frequency, the dielectric constant and frequency of the produced nanoparticles drop. The kinetic analysis yields a rate constant of 0.0165 min -1 for nanosphere-like particles. At a concentration of 1% Au, the produced nanoparticles degrade the dye completely in 150 minutes when exposed to UV light.